A Structural Topic Model Analysis of Privacy in Mandarin Chinese News: 2010–2019. Issue 1 (13th October 2021) - Ma, Yuanye
Abstract: This poster presents a study that analyzes privacy using a 10‐year privacy news corpus in Mandarin Chinese, using an unsupervised machine learning technique, structural topic modeling (stm). The 13 topics revealed several dimensions for understanding privacy in the Chinese language, including how privacy is concerned, by who, and in what context/domain. This study is one of the first empirically‐rounded explorations of the concept of privacy in the current Chinese language. Findings from this study could be used to further the discussion and investigation to understand privacy as an intercultural information ethics concept.